Mobility of the {0110} inversion domain boundary in ZnO nanopillars - Wang, J.; Zhou, M.; Yang, R.; Xiao, P.; Ke, F.; Lu, Chunsheng (2021)
The apparent activation energy of a nanostructure is difficult to directly measure experimentally. In this letter, we present a computational method for estimating the apparent activation energy of a range of semiconductor nanostructures. This method allows the activation energy to be obtained from experimentally measured average activation time or propagation speed at various temperatures of the phase boundary associated with the transformation. The approach entails analyzing the mobility of the transformation in question using a model based on the Arrhenius relation. The specific analysis carried out uses the {0110} inversion domain boundary in wurtzite ZnO nanopillars as example. Molecular dynamics simulations are conducted over the temperature range of 300–900 K of the corresponding available experimental data. The approach and analysis offer a means for experimentally establishing the apparent activation energy of the {0110} inversion domain boundary in a variety of wurtzite-structured II-VI, III-V and IV-IV binary compounds.